Spiritual practices as coping with mothers of children with attention-deficit hyperactivity disorder: a qualitative explorative study - K. V. G. S. G. Vithana; T. A. Asurakkody (BMC Psychology)
Abstract Background Mothers of children with ADHD struggle with everyday challenges that exceed from the signs and symptoms of ADHD. They have applied different coping mechanisms, comprising spiritual practice commitments. The study aims to explore spiritual practices as a coping mechanism for mothers of children with ADHD. Method Qualitative exploratory research methodology was conducted with 22 mothers who were selected via purposive sampling. Semi-structured interviews were conducted, and the data were analysed via thematic analysis. Results The findings were discussed with three main themes and six subthemes:01) cognitive appraisal—thinking with faith and belief about higher power; 2) behavioral practices—individual practices and group approaches; and 3) support from religious leaders—common support with religious concepts and specific personnel support. Conclusions This study discussed the religious commitment as coping of mothers, who used them as coping mechanisms while caring for a child with ADHD. They found a variety of culturally bound religious practice methods that were reported to be perceived as effective for their mental well-being.